1978
DOI: 10.1007/bf00120935
|View full text |Cite
|
Sign up to set email alerts
|

Feeding the information eaters: Suggestions for integrating pure and applied research on language comprehension

Abstract: This paper examines the current relation between pure and applied research on the comprehension of written information. It finds few points of contact. The suggestion is put forward that greater interaction could be mutually profitable. An information flow among researchers is proposed that starts with applied solutions to practical problems, continues through pure explanations of why these solutions are successful, and so enables the refinement of the original applied solutions. Because such an information fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1979
1979
2005
2005

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 96 publications
0
11
0
1
Order By: Relevance
“…Complexity metrics have been theoretically derived from specific linguistic theories, experimentally devised from models of syntactic processing, and empirically developed from research on language acquisition and sentence processing (Cheung & Kemper, 1992). Complexity metrics are typically combined with a "redesign-test" procedure (Wright, 1978) in order to validate the metric as a guide for enhancing reading Downloaded by [York University Libraries] at 05:16 03 January 2015 speed and/or accuracy. Alternatively, reading researchers have commonly developed readability formulas to measure the overall difficulty, or the grade level suitability, of reading materials (Bruce & Rubin, 1988;Duffy, 1985).…”
mentioning
confidence: 99%
“…Complexity metrics have been theoretically derived from specific linguistic theories, experimentally devised from models of syntactic processing, and empirically developed from research on language acquisition and sentence processing (Cheung & Kemper, 1992). Complexity metrics are typically combined with a "redesign-test" procedure (Wright, 1978) in order to validate the metric as a guide for enhancing reading Downloaded by [York University Libraries] at 05:16 03 January 2015 speed and/or accuracy. Alternatively, reading researchers have commonly developed readability formulas to measure the overall difficulty, or the grade level suitability, of reading materials (Bruce & Rubin, 1988;Duffy, 1985).…”
mentioning
confidence: 99%
“…Our results showed that in nine out of these 11 cases the readers judged the active sentences to be more readable. Wright (1978) pointed out that a useful procedure to use to assess the readability of text was to ask readers to point out those places where they thought that other readers might have difficulties. (This procedure gets around the problem of people being unwilling to say that they themselves cannot understand parts of the material.…”
Section: Results: (3) Comparison Of Original and Revised Sentencesmentioning
confidence: 99%
“…Elsewhere in a discussion of the value of pooling the skills of those working on different aspects of human communication I explored the analogy of 'feeding the information eaters' and suggested the need for 'greater co-operation between those studying the digestibility of information (psychologists), those training people to eat more wisely (educationists) and those who select and blend the ingredients of written communications (writers and information designers)' (Wright, 1978). This was not intended as an exhaustive list, but serves to illustrate that these disciplines cannot be substituted for each other, nor does it make much sense to argue about their relative importance.…”
Section: Polymathsmentioning
confidence: 99%